A heterotrimeric death domain complex in Toll signaling - Sun, Huaiyu (The National Academy of Sciences, 2002)
Signaling from the transmembrane receptor Toll to Rel-related transcription factors regulates dorsoventral patterning of the Drosophila embryo, as well as larval and adult immunity. To identify additional pathway components, we have used double-stranded RNA interference to investigate Drosophila counterparts of genes that regulate the mammalian Rel family member NF-κB. Experiments in cultured cells reveal that the fly orthologue of the adaptor protein MyD88 is essential for signal transduction from Toll to a second adaptor protein, Tube. By using coimmunoprecipitation studies, we find a heterotrimeric association of the death domains of MyD88, Tube, and the protein kinase Pelle. Site-directed mutational analyses of interaction sites defined by crystallographic studies demonstrate that Tube recruits MyD88 and Pelle into the heterotrimer by two distinct binding surfaces on the Tube death domain. Furthermore, functional assays confirm that the formation of this heterotrimer is critical for signal transduction by the Toll pathway.